Standardization of protocol for in-vitro shoot tip grafting in Kinnow mandarin (Citrus deliciosa) - KUMAR, RAJ; KAUL, M K; SAXENA, S N; SINGH, A K; KHADDA, B S (The Indian Journal of Agricultural Sciences, 2014)
An experiment to standardize the rootstocks and PGRs for success and survival of in-vitro shoot tip grafting in Kinnow mandarin (Citrus deliciosa) was conducted during the year of 2007-08 at Department of Horticulture, Agricultural Research Station, Sriganganagar, Rajasthan. For this, in-vitro generated and 2-3 weeks etiolated old seedlings of cleopatra, rough lemon and carrizo were used as rootstocks. The seedlings were grafted by shoot tips measuring = 1 mm in length containing apical meristem and one or two leaf primordial which were excised from in-vitro generated shoots and grafted on rootstocks. Among different rootstocks used, twelve days old seedlings of Carrizo recorded the maximum success (56.60 %) and length of shoot (1.43 cm). All the concentrations of the PGRS tried to accelerate the growth of new shoot and survival per cent of STG, BAP @ 1.0 mg/l was found to be best in minimizing the time taken to bud break (12.12 days) and recorded maximum shoot length (3.10 cm). The results of the study revealed that the maximum survival (66.90 %) was observed with 2, 4-D @ 3.0 mg/l in all the PGRs tried for growth promotion of scion shoots. It is also revealed from the study that the 90 % grafted plants survival in greenhouse at after 45 days after shoot tip grafting. Based on the observations, the Carrizo as rootstocks, BAP and 2, 4-D were found to be the best protocol for shoot tip grafting in Kinnow mandarin.